Sustainable Tourism in the Age of Innovation: A Bibliometric Exploration of Progress and Potential - Tuyen, Tran (Journal of Tourism, Sustainability and Well-being, 2025)
Innovation has become a defining trend across various socio-economic sectors, including tourism, where it plays a crucial role in enhancing efficiency, reducing costs, and maintaining competitiveness. Within the tourism industry, innovation encompasses technological advancements, strategic planning, and new business models aimed at optimizing operations and fostering sustainable development. However, despite the increasing recognition of tourism innovation and sustainability, there remains a limited understanding of how these two concepts intersect. While existing studies highlight the importance of innovation in tourism, research on its direct contribution to sustainable development is still fragmented. A more structured and comprehensive analysis is needed to bridge this gap and provide a clearer understanding of the evolving relationship between innovation and sustainability in tourism. To address this issue, this study conducts a semi-systematic literature review combined with bibliometric analysis of 181 publications sourced from the Scopus database. The findings reveal a growing body of research focused on technology adoption, digital transformation, corporate governance, destination management, and co-creation, all of which indicate a shift toward sustainability-driven innovation. This study makes two key contributions. Theoretically, it maps emerging research trends and identifies key thematic clusters, offering a structured framework for understanding innovation in sustainable tourism. Practically, it provides strategic insights for tourism businesses and policymakers, emphasizing technology integration, stakeholder collaboration, and sustainability-driven innovation as crucial for industry resilience.